The Influence Of Fintech On The Development Of Islamic Financial Inclusion In Msmes In Tanak Awu Village - Ahadiah Agustina (Jurnal Ilmiah Ekonomi Islam, 2023)
line with this, Fintech has emerged as one of the impacts of increasingly modern technological developments, especially in terms of finance. Fintech is here to answer people's needs for the importance of convenience in every economic process that involves Islamic finance. Sharia-based fintech will further increase financial inclusion in MSMEs because financial management managed by sharia is in accordance with religious guidelines, so that it will have a good impact on MSME financial management. Good management will also have a good impact on increasing MSMEs so that it will increase economic stability in Indonesia. The purpose of this study was to determine fintech management (risk and investment management, market provisioning, and cashless society) on Islamic financial inclusion (financial knowledge, financial behavior, and financial attitude) in MSMEs in the city of Mataram. The research conducted includes the type of quantitative research. The population of this research is the MSME industry in Tanak Awu village by focusing on using archival data (archival method). This study uses descriptive analysis and classical assumption test. The plan in this study is to determine the simultaneous and partial effect of fintech variables (risk and investment management and market provisioning) on Islamic financial inclusion (knowledge of Islamic finance, financial behavior, and financial attitudes).